In vitro activity of tigecycline, a new glycylcycline, tested against 1,326 clinical bacterial strains isolated from Latin America - Gales, Ana Cristina [UNIFESP] (2005)
The in vitro activity of tigecycline (former GAR-936), a new semisynthetic tetracycline, was evaluated in comparison with tetracycline and other antimicrobial agents. MATERIAL AND METHODS: A total of 1,326 contemporary clinical isolates collected from the Latin American region were collected in 2000-2002 period and tested with microdilution broth according to the CLSI guidelines. The bacterial pathogens evaluated included Staphylococcus aureus (505), Streptococcus pneumoniae (269), coagulase-negative staphylococci (CoNS; 227), Haemophilus influenzae (129), Enterococcus spp. (80), Moraxella catarrhalis (54), beta-haemolytic streptococci (28), viridans group streptococci (26), and Neisseria meningitidis (8) RESULTS:Tigecycline demonstrated excellent activity against all Gram-positive cocci, with 90% of penicillin-resistant S. pneumoniae strains being inhibited at 0.12 µg/mL, while the same isolates had an MIC90 of > 16 µg/mL for tetracycline. All Enterococcus spp. were inhibited at 0.25 µg/mL of tigecycline. Tigecycline (MIC50, 0.25 µg/mL) was eight-fold more potent than minocycline (MIC50, 2 µg/mL) against oxacillin-resistant S. aureus (ORSA); all ORSA were inhibited at < 2 µg/mL of tigecycline. Tigecycline demonstrated excellent activity (MIC50, 0.5 µg/mL) against CoNS with reduced susceptibility to teicoplanin (MIC, 16 µg/mL). Tigecycline also showed high potency against respiratory pathogens such as M. catarrhalis (MIC50, 0.12 µg/mL) and H. influenzae (MIC50, 0.5 µg/mL). No tigecycline resistant isolates were detected when the proposed susceptible breakpoints (< 4 µg/mL) was applied. CONCLUSIONS: This results indicate that tigecycline has potent in vitro activity against clinically important pathogenic bacteria, including Gram-positive isolates resistant to both tetracycline and minocycline.